Safety and efficacy of substance-based medical devices: Design of an in vitro barrier effect test - Bassetto, Rebecca; Perin, Stefano; Amadio, Emanuele; Zanatta, Samuele; Nenzioni, Davide; Bertin, Walter (Frontiers in Drug Safety and Regulation, 2023)
This study aims to develop an in vitro barrier effect test over biomimetic membrane, which is useful to establish the film forming ability of a substance-based medical device (SB-MD). The method contemplates a multiparametric approach including: i) the measurement of the transmembrane passage of a molecular-like marker over a lipid-impregnated biomimetic membrane (simulating the skin and gastro-intestinal and buccal tissues) by using a static diffusion cell apparatus (Franz cell); and ii) the evaluation of the integrity of the membrane (colorimetric test). In the first step, a series of lipid-impregnated biomimetic membranes (simulating gastro-intestinal, buccal, and skin tissues) were implemented and their permeability performance validated using model drugs (caffeine and acyclovir) by referring to literature data. As a result, the apparent permeability (Papp) of caffeine over the biomimetic gastro-intestinal membrane (Papp = 30.5E-6 cm/s) was roughly comparable to the literature values obtained with Caco-2 cell line membrane (Papp = 30.8E-6 cm/s) and with the Franz cell method (Papp = 36.2E-6 cm/s). Acyclovir was shown to be a poorly permeable substance both in the literature and experimental data. Following this step, the permeability study was extended to both biomimetic buccal and skin (STRAT-M®) membranes: for caffeine, biomimetic gastro-intestinal membrane was the most permeable (Papp = 30.5E-6 cm/s), followed by the buccal (Papp = 18.2E-6 cm/s) then the skin (Papp = 0.5E-6 cm/s) biomimetic membranes. In a second part of the work, the barrier effect test was developed following a similar permeability-like approach. The protocol was designed with the idea of assessing the capacity of a certain product to prevent the passage of caffeine across the biomimetic membrane with respect to a negative and positive control. The untreated membrane was the negative control, while membrane covered with a Vaseline film was the positive. As a last step, the developed barrier effect protocol was applied to an experimental gel-like SB-MD under development for the treatment of aphthae (Aphthae gel, an invented trade name), herein used as a case study. Regarding the results, Aphthae gel reduced the caffeine passage by 60.3%, thus highlighting its effectiveness to form a protective film. Overall, these results provide important knowledge and may pave the way for the use—including for industrial applications—of these simple but effective biomimetic membranes for carrying out high throughput screening necessary to design safe and effective SB-MDs before proceeding further with clinical trials, as requested by the regulations.